Glaulactams A–C, daphniphyllum alkaloids from Daphniphyllum glaucescens. Issue 1 (December 2018) - Chao, Chih-Hua; Cheng, Ju-Chien; Gonçalves, Théo; Huang, Kuo-Wei; Lin, Chi-Chien; Huang, Hui-Chi; Hwang, Syh-Yuan; Wu, Yang-Chang
Abstract Glaulactams A–C (1–3), which possess a novel skeleton, as well as the known compound daphmanidin B (4), were isolated from the leaves ofDaphniphyllum glaucescens and separated using ion-exchange chromatography aided by NMR fingerprinting. Their structures, including their absolute configurations, were elucidated by spectroscopic analyses and time-dependent density-functional-theory-calculated electronic circular dichroism spectra; the data were subsequently analyzed to gain insight into the respective biogenetic relationships between the isolates, which exhibited anti-H1N1 and immunosuppressive activities.